1997
DOI: 10.1021/jo962101e
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Nitric Oxide with Amines

Abstract: Reactions of nitric oxide (NO) with amines in organic solvents were studied using Hantzsch dihydropyridines and aromatic primary amines as substrates. Hantzsch dihydropyridines are readily oxidized by nitric oxide to give the corresponding pyridines in quantitative yields. The addition of oxygen accelerates the reaction rate considerably. On the other hand, aromatic primary amines give deaminated products by the reaction with nitric oxide only in the presence of oxygen in ethereal solvents or chloroform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
82
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 31 publications
3
82
0
1
Order By: Relevance
“…This is in agreement with the observation made by others employing different oxidative conditions [3]. However, aryl substituted 1,4-dihydropyridines (Entries 4-12, 14, 15 and 18-24) furnished the corresponding pyridine derivatives (Tables 1-4).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with the observation made by others employing different oxidative conditions [3]. However, aryl substituted 1,4-dihydropyridines (Entries 4-12, 14, 15 and 18-24) furnished the corresponding pyridine derivatives (Tables 1-4).…”
Section: Resultssupporting
confidence: 93%
“…Another major drawback to the older procedures is their use of reagents that are either highly toxic or present serious disposal problems (or both). One example is NO gas, which is corrosive, highly toxic and must therefore be used under Ar atmosphere in an effective hood with great caution [3]. Exceptions are the recent reports by Hayashi et al, who reported the remarkably practical use of O 2 gas and NO gas as clean and efficient oxidants for this purpose [1,3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the corresponding pyridine derivatives show antihypoxic and anti-ischemic activities and are used in the treatment of atherosclerosis [11]. Additionally, dihydropyridines are often produced in a synthetic sequence and have to be oxidized to pyridines [12]. Numerous reagents and procedures have been recommended for this purpose, such as pyridinium chlorochromate (PCC) [13], N 2 O 4 complex of 18-crown-6 [14], tert-butylhydroperoxide [15], photochemical oxidation [16], vanadium(V) salts [17], and biomimetic catalyzed oxidation [18].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Dihydropyridines are usually subsequently oxidized to pyridines. [6] Many classical methods for the synthesis of symmetrical 1,4-dihydropyridines have been reported [7][8][9][10][11] based on conventional heating of a b-keto ester, an ammonium salt and an aldehyde in organic solvents, but most of these methods involve long reaction times, harsh reaction conditions and generally lead to low yields. Therefore, it is necessary to develop more efficient and versatile methods for the preparation of 1,4-dihydropyridines and the progress in this field has been recently achieved by the use of promoters such as microwaves, [6b,12] TMSCl, [5] ionic liquids, [13,14] polymers [15,16] and YbA C H T U N G T R E N N U N G (OTf) 3 .…”
mentioning
confidence: 99%